Court-ship, kinship and business: A study on the interaction between the formal and the informal institutions and its effect on entrepreneurship - Tanika Chakraborty; Anirban Mukherjee; Sarani Saha (IZA Journal of Labor & Development, 2015)
In this paper we theoretically and empirically examine how the interaction between the formal court system and the informal loan network affects a household's decision to start a business. We find that when the formal court system is weak, expansion of informal credit network leads to the proliferation of business. However, with a sufficiently strong court system, expansion of the credit network has a negative effect on business prospects. This result is explained by the contradictions between formal laws and norms used by informal networks.
Keywords: K12; L26; O17; 330; Informal network; Court; Formal institution; Entrepreneurship